PENGARUH LOKASI FASILITAS DAN PROMOSI TERHADAP DAYA TARIK PENGUNJUNG PANTAI PASAR SELUMA - Nopi Indar Pertiwi; khairul Bahrun; Adi Sismanto (UM. Bengkulu, 2023)
Research on Pasar Seluma Beach visitors has the following problem formulation, how does the location, tourist facilities and promotion influence simultaneously on Pasar Seluma Beach tourism? This study aims to determine the effect of location, tourist facilities and tourism promotion on the Tourism Attractivenessof Pasar Seluma Beach. The sample used was calculated using the Lemeshow formula (Lemeshow, 199) based on predetermined criteria totaling 161 respondents. Data collection techniques were carried out through observation, documentation and questionnaires. The processed data was analyzed using the SPSS 25 formula.Based on the regression results it is known that the significant value for the effect of X1, X2 and X3 together on Y is 0.00. The F-count value is 70.899 and the F-table value is 3.90. Thus, the F-count value (70.899) > F-table (3.390) with a significant value of 0.00 > 0.05, then H0 is rejected and H3 is accepted. It can be concluded that X1, X2 and X3 have a significant effect on Pasar Seluma Beach Tourism Attractiveness. Keywords : Location, Facilities, Promotion and Attraction